2023
DOI: 10.1002/smll.202303596
|View full text |Cite
|
Sign up to set email alerts
|

Novel PdPtCu Nanozymes for Reprogramming Tumor Microenvironment to Boost Immunotherapy Through Endoplasmic Reticulum Stress and Blocking IDO‐Mediated Immune Escape

Abstract: Breaking immunosuppressive tumor microenvironment (TME) has unique effects on inhibiting tumor growth and recurrence. Here, an endoplasmic reticulum (ER) targeted PdPtCu nanozyme (PNBCTER) is prepared to boost immunotherapy. First, PNBCTER has three kinds of enzyme activities, including catalase (CAT), glutathione oxidase (GSHOx), and peroxidase (POD)‐like activities, which can reshape the TME. Second, PNBCTER kills tumor cells by photodynamic therapy (PDT) and photothermal therapy (PTT). Third, guided by TER,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Nevertheless, practical applications of immunotherapy often encounter challenges including low efficacy in inducing immune responses and potential effects related to immunity regulation. 237,238 Fortunately, nanozymes with intrinsic enzyme-like activity have emerged as promising agents capable of reversing the immunosuppressive microenvironment in vivo, thereby addressing the limitations associated with conventional immunotherapy. 239 For example, 240 The resulting DNA damage triggered cGAS-mediated production of 2′,3′-cGAMP, which subsequently activated STING, thereby achieving immune modulation within the tumor microenvironment.…”
Section: Chemodynamic Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, practical applications of immunotherapy often encounter challenges including low efficacy in inducing immune responses and potential effects related to immunity regulation. 237,238 Fortunately, nanozymes with intrinsic enzyme-like activity have emerged as promising agents capable of reversing the immunosuppressive microenvironment in vivo, thereby addressing the limitations associated with conventional immunotherapy. 239 For example, 240 The resulting DNA damage triggered cGAS-mediated production of 2′,3′-cGAMP, which subsequently activated STING, thereby achieving immune modulation within the tumor microenvironment.…”
Section: Chemodynamic Therapymentioning
confidence: 99%
“…Immunotherapy aims to enhance antitumor responses by engaging both innate and adaptive immune systems through strategies such as administering immune checkpoint inhibitors like anti-PD-1 or anti-PD-L1 antibodies. Nevertheless, practical applications of immunotherapy often encounter challenges including low efficacy in inducing immune responses and potential effects related to immunity regulation. , Fortunately, nanozymes with intrinsic enzyme-like activity have emerged as promising agents capable of reversing the immunosuppressive microenvironment in vivo , thereby addressing the limitations associated with conventional immunotherapy . For example, Zhang et al reported a Co,N-doped carbon dot exhibiting POD-like activity capable of catalyzing H 2 O 2 to generate ROS and induce DNA damage .…”
Section: Application Of Nanozymes In Enhancing Anticancer Effectsmentioning
confidence: 99%
“…Nanozymes, that is, nanomaterials containing enzyme-like activity [18][19][20][21], have grown quickly and are now frequently employed in the field of tumor research [22][23][24]. Precious metal nanozymes are a kind of nanomaterials containing noble metals elements (Au, Ag, Pt, Pd, etc) [25][26][27][28][29], which generally have extensive absorption spectrum and excellent photothermal performance, endowing them with the potential of photothermal agent for PTT [30].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Furthermore, endoplasmic reticulum (ER) stress would induce ICD effectively, where dying tumor cells release damage-associated molecular patterns (DAMPs), such as calreticulin (CRT), adenosine triphosphate (ATP), and high mobility group box 1 (HMGB1). [19][20][21][22] Thence, ER stress is a crucial factor to determine the efficiency of immunotherapy.…”
Section: Introductionmentioning
confidence: 99%